2014
DOI: 10.4103/1817-1745.139326
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis: Extremely rare presentation of pediatric human immunodeficiency virus infection

Abstract: Acquired human immunodeficiency virus (HIV) infection in a 10-year-old child, presenting with monoparesis, progressing to triplegia over 4 weeks is an extremely rare feature. The child had left upper motor neurone facial palsy with left hemiplegia, paralyzed right lower limb, grade zero power, exaggerated deep tendon reflexes and bilateral extensor plantars. Child tested positive for HIV by ELISA. CD3+ absolute count was 431. CD3+ CD4 count was 28, and CD45 absolute count was 478. Magnetic resonance imaging of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the literature, cases with facial paralysis have rarely been reported. However, the association between facial paralysis and ADEM was not explained clearly (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, cases with facial paralysis have rarely been reported. However, the association between facial paralysis and ADEM was not explained clearly (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Tripathy et al (14) reported a 36-year-old male with behavioral abnormalities, hemispatial neglect of left upper limb, paralysis of the left facial nerve, left arm, and right leg. Patra et al (15) reported a 10-year-old child who had left upper motor neuron facial palsy with left hemiplegia, paralyzed right lower limb, exaggerated deep tendon reflexes, and bilateral extensor plantar responses. Kaymakamzade et al (16) reported a 25-yearold male with bilateral central facial palsy and severe quadriparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of these three cases, only one had ADEM associated with primary HIV infection. Patra et al reported a 10-yearold HIV-infected child presenting with monoparesis and progressing to triplegia over four weeks [40]. Serological IgM titers for Toxoplasma gondii, Treponema pallidum, Cytomegalovirus and the hepatitis B, rubella and herpes simplex and hepatitis C viruses, Mantoux test, and the hepatitis B surface antigen were negative.…”
Section: Acute Disseminated Encephalomyelitismentioning
confidence: 99%
“…ADEM presents with multiple manifestations including encephalopathy coupled with evidence of multifocal lesions of demyelination on neuroimaging. ADEM in children has been reported following exanthematous viral infections, systemic infections or recent vaccinations and is postulated to be due to the immune system dysregulation 1. Although ADEM can occur at all ages, it is most commonly reported in children and adolescents with an incidence rate of 8 per 1 000 000 people per year 2.…”
Section: Introductionmentioning
confidence: 99%